Clinicopathologic Features and Risk Factors for Recurrence of Mucinous Borderline Ovarian Tumors: A Retrospective Study With Follow-up of More Than 10 Years. Issue 9 (November 2018) - Sun, Li; Li, Ning; Song, Yan; Wang, Guixiang; Zhao, Zitong; Wu, Lingying
Abstract : Objective: This study aimed to evaluate the clinicopathologic features of mucinous borderline ovarian tumors (MBOTs), with an emphasis on the risk factors for recurrence. Methods: Data of 76 patients with MBOT diagnosed and treated between 2000 and 2007 at a single institution were analyzed in this retrospective study. The clinicopathologic features of different tumor subgroups were analyzed, including pathology, surgical methodology, recurrence, and overall survival. Results: The median patient age was 40 years (13–85 years). Forty-six patients with gastrointestinal mucinous borderline tumors (intestinal MBOTs) (73.7%) and 20 patients with endocervical MBOT (26.3%) were identified. Forty radical surgeries and 26 conservative surgeries were performed. There were 74.6% patients (50/67) with stage I disease among the 67 patients who received comprehensive surgical staging. During a median follow-up time of 151 months, 9 recurrences were identified. Median duration from surgery to recurrence was 26.4 months (range, 13–50 months). There was no difference in recurrence rate between intestinal MBOT and endocervical MBOT (14.3% vs 5.0%; P > 0.05). The recurrence rate of stage III tumors was significantly higher than that of stage I (33.3% vs 8%; P < 0.05). The recurrence rate after conservative surgery was higher than that after radical procedures (21.4% vs 6.3%; P < 0.05). Conclusions: The majority of patients with MBOT had a favorable prognosis. Patients with later-stage disease had a higher recurrence rate. Abstract : Based on a population-based sample of 2490 ovarian cancer patients, the prognosis is better for MBOTs than typical ovarian tumors; late-stage combined with peritoneal pseudomyxoma is a high-risk factor for the recurrence of MBOT.